Modeling the carbon and nitrogen cycles - Varotsos, Costas A.; Krapivin, Vladimir F.; Soldatov, Vladimir Y. (Frontiers in Environmental Science, 2014)
The issues of air pollution are inextricably linked to the mechanisms underlying the physicochemical functioning of the biosphere which together with the atmosphere, the cryosphere, the lithosphere, and the hydrosphere constitute the climate system. We herewith present a review of the achievements and unresolved problems concerning the modeling of the biochemical cycles of basic chemicals of the climate system, such as carbon and nitrogen. Although the achievements in this area can roughly describe the carbon and nitrogen cycles, serious problems still remain associated with the accuracy and precision of the processes and assessments employed in the relevant modeling.